2014
DOI: 10.1016/j.bbalip.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the loss of caveolin-1 on lung mass and cholesterol metabolism in mice with and without the lysosomal cholesterol transporter, Niemann–Pick type C1

Abstract: Caveolin-1 (Cav-1) is a major structural protein in caveolae in the plasma membranes of many cell types, particularly endothelial cells and adipocytes. Loss of Cav-1 function has been implicated in multiple diseases affecting the cardiopulmonary and central nervous systems, as well as in specific aspects of sterol and lipid metabolism in the liver and intestine. Lungs contain an exceptionally high level of Cav-1. Parameters of cholesterol metabolism in the lung were measured, initially in Cav-1-deficient mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…These values were not corrected by HPBCD therapy which has also been found by others [12]. Severity of lung disease was enhanced by concomitant absence of caveolin [13] which is normally increased in Npc1 −/− mouse livers [14] and even heterozygous NPC1 fibroblasts [15]. …”
Section: Introductionsupporting
confidence: 53%
“…These values were not corrected by HPBCD therapy which has also been found by others [12]. Severity of lung disease was enhanced by concomitant absence of caveolin [13] which is normally increased in Npc1 −/− mouse livers [14] and even heterozygous NPC1 fibroblasts [15]. …”
Section: Introductionsupporting
confidence: 53%
“…Additionally, the reduced density of oligodendrocytes in white matter structures of Npc1 −/− mice ( Weintraub et al, 1987 ; Takikita et al, 2004 ; Yan et al, 2011 , 2014 ; Yu and Lieberman, 2013 ; Bernardo et al, 2021 ; Kunkel et al, 2023 ) should contribute to reduced fresh volume. In Npc1 −/− mice, from early postnatal development onwards, defects of differentiation of post-mitotic pre-myelinating oligodendrocytes into mature myelinating oligodendrocytes have been described by various groups ( Weintraub et al, 1987 ; Takikita et al, 2004 ; Miller and Auchus, 2011 ; Yan et al, 2011 , 2014 ; Hedrich, 2012 ; Yu and Lieberman, 2013 ; Mundy et al, 2014 ; Bernardo et al, 2021 ; Kunkel et al, 2023 ). As also seen in the present study, the amount of hypomyelination varied between different parts of the brain ( Payne and Hales, 2004 ; Miller, 2013 ; Cole et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that CAV-1 protein overexpression markedly reduced total cholesterol and free cholesterol (FC) content as well as their accumulation in lipid-loading cells [ 6 8 ]. In CAV-1-deficient mice, moderately elevated whole-lung cholesterol content, impaired liver regeneration, cardiovascular disorders, and FC accumulation in mitochondrial membranes resulted in mitochondrial diseases [ 9 11 ]. However, Frank et al .…”
Section: Introductionmentioning
confidence: 99%